Perineal Trauma in a Low-risk Maternity with High Prevalence of Upright Position during the Second Stage of Labor - Peppe, Mariana Vitor; Stefanello, Juliana; Infante, Bruna Fregonesi; Kobayashi, Mauricio Tsuguio; Baraldi, Claudia de Oliveira; Brito, Luiz Gustavo Oliveira (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2018)
Objective Perineal trauma is a negative outcome during labor, and until now it is unclear if the maternal position during the second stage of labor may influence the risk of acquiring severe perineal trauma. We have aimed to determine the prevalence of perineal trauma and its risk factors in a low-risk maternity with a high incidence of upright position during the second stage of labor.Methods A retrospective cohort study of 264 singleton pregnancies during labor was performed at a low-risk pregnancy maternity during a 6-month period. Perineal trauma was classified according to the Royal College of Obstetricians and Gynecologists (RCOG), and perineal integrity was divided into three categories: no tears; first/second-degree tears + episiotomy; and third and fourth-degree tears. A multinomial analysis was performed to search for associated factors of perineal trauma.Results From a total of 264 women, there were 2 cases (0.75%) of severe perineal trauma, which occurred in nulliparous women younger than 25 years old. Approximately 46% (121) of the women had no tears, and 7.95% (21) performed mediolateral episiotomies. Perineal trauma was not associated with maternal position (p = 0.285), health professional (obstetricians or midwives; p = 0.231), newborns with 4 kilos or more (p = 0.672), and labor analgesia (p = 0.319). The multinomial analysis showed that white and nulliparous presented, respectively, 3.90 and 2.90 times more risk of presenting perineal tears.Conclusion The incidence of severe perineal trauma was low. The prevalence of upright position during the second stage of labor was 42%. White and nulliparous women were more prone to develop perineal tears.
Keywords: perineal trauma; retrospective cohort study; birth position; obstetric anal sphincter injuries